Peran Komunikasi Lingkungan Strategis dalam Mitigasi Penularan Demam Berdarah - Theresia, Santi; Octoviani, Fanny Anggraeni; Herdiansyah, Haris (Expose: Jurnal Ilmu Komunikasi, 2023)
Dengue fever remains a significant public health challenge, particularly in tropical countries like Indonesia. This study investigates the role of environmental and communication strategies in mitigating dengue fever transmission in Jababeka, Cikarang, an area with high urbanization and dengue incidence. Using a cross-sectional observational design, the research combines environmental surveys and evaluations of health communication strategies. Key findings indicate a high House Index (HI) of 12.5%, exceeding the critical risk threshold of 10%. The primary mosquito breeding sites were identified as outdoor containers such as unused buckets, discarded tires, and flower pot trays. Communication strategies like the "3M" campaign were widely known, but only a minority consistently adopted preventive measures, indicating gaps between knowledge and practice. The study highlights the need for community-centered, culturally sensitive, and technologically innovative approaches to enhance awareness and participation in dengue prevention. Strengthening collaboration between communities, governments, and stakeholders is essential to achieve sustainable mitigation outcomes.